Impact of renewable energy sources technologies on power system stability: a Moroccan case study - Ismail Drhorhi; Abderrahim El Fadili (Institute of Advanced Engineering and Science, 2022)
Most countries of the world have adopted renewable energy sources (RES) because of consistent policy and industry support. The use of these sources is expanding and will cover a larger part of the generation capacity in the future. Thus, power systems (PS) are experiencing the high scale RES integration. For a power system dominated by RES, the electrical grid characteristics, namely, the inertia constant (Hs) and the rate of change of frequency (ROCOF), should be evaluated. Furthermore, the requirements related to these characteristics should be specified in the grid code (GC) to reflect the actual needs of the transmission system operator (TSO) and to prepare the evolution of the RES penetration level. Due to the delay in specifying or updating these GC requirements, RES that are incorporating unsuitable functionalities for the future perspective, regarding fault-ride-through (FRT) and frequency support requirements, will remain operational by 2030; this will create additional constraints on the PS frequency stability after large-scale RES integration. In this paper, the impact assessment of deployed RES technologies on the Moroccan PS frequency stability is assessed by the year 2030, using MATLAB/Simulink environment. The main reason for focusing on the case study of Morocco is the country’s target of installing 52% of the energy supply from RES in the horizon of 2030.